Ofatumumab and Lenalidomide for Patients with Relapsed or Refractory Chronic Lymphocytic Leukemia: Correlation between Responses and Immune Characteristics - Vitale, Candida (Clin Cancer Res, 2016)
PURPOSE: We evaluated efficacy and tolerability of the combination of ofatumumab and lenalidomide in patients with relapsed/refractory chronic lymphocytic leukemia (CLL), and explored whether immune system characteristics could influence the response to treatment. EXPERIMENTAL DESIGN: Thirty-four patients were enrolled in this phase II study. Ofatumumab was administered at a dose of 300 mg on day 1, 1,000 mg on days 8, 15, and 22 during course 1, 1,000 mg on day 1 during courses 3–6, and once every other course during courses 7–24 (28-day courses). Oral lenalidomide (10 mg daily) was started on day 9 and continued for as long as a clinical benefit was observed. RESULTS: The overall response rate was 71%. Eight patients (24%) achieved a complete remission (CR) or CR with incomplete recovery of blood counts, including 9% with minimal residual disease-negative CR. The median progression-free survival was 16 months, and the estimated 5-year survival was 53%. The most common treatment-related toxicity was neutropenia (grade >2 in 18% of the 574 patient courses). The most frequent infectious complications were pneumonia and neutropenic fever (24% and 9% of patients, respectively). We observed that patients who achieved a CR had at baseline higher numbers and a better preserved function of T cells and natural killer cells compared with non-responders. CONCLUSIONS: The combination of ofatumumab and lenalidomide is a well-tolerated regimen that induces durable responses in the majority of patients with relapsed/refractory CLL. Our correlative data suggest a role of competent immune system in supporting the efficacy of this treatment.